(untitled) (Research, Society and Development, 2021)
Introduction: Population aging has gained considerable prominence in recent years due to increased life expectancy and modernization of technologies. According to the Ministry of Health, Brazil has the fifth largest elderly population in the world, with about 28 million people aged 60 years and over. Objective: to analyze the evidence through a literature review on the quality of life of caregivers of the elderly, identifying the main comorbidities between them and their age group. Methodology: This is a literature review using the Lilacs, Academic Google, Scientific Electronic Library Online – SciELO, US National Library of Medicine Nacional Institutes of Health (PubMed), Index Psicologia and Coleciona SUS data bases, from 2010 to 2021. 18 articles were analyzed. Results and discussion: It was identified that the main factors that influenced the quality of life varied between the burden and the bond created between the caregiver and the elderly. Also, the main comorbidities found among caregivers are: cardiovascular, psychiatric and musculoskeletal diseases. Conclusion: There is a need for a more careful look at the quality of life of caregivers of the elderly due to the damage to their health, whether physical or emotional. Enabling health professionals to carry out intervention strategies in order to create therapeutic bonds with the families of the elderly, identifying their needs, and thus, reducing stress and burden.